2022
DOI: 10.1111/jsr.13682
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of home sleep apnea testing using peripheral arterial tonometry for sleep apnea: A systematic review and meta‐analysis

Abstract: Summary This study aimed to evaluate the diagnostic accuracy of home sleep apnea testing using peripheral arterial tonometry for sleep apnea as an alternative to polysomnography. We conducted a systematic review and meta‐analysis of observational studies, randomized controlled trials, and diagnostic case–control studies examining the diagnostic accuracy of peripheral arterial tonometry by searching the CENTRAL, MEDLINE, EMBASE, ICTRP and http://clinicaltrials.gov databases on 5 October 2021. We assessed the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Comparable data for negative PAT were found in the PATER study [ 31 ]. Previous studies have shown that PAT has a good sensitivity for an AHI ≥ 5/h (pooled sensitivity of 96%; CI 93–97%) [ 52 ]. The focus of our study was to determine how a positive PAT result (≥ 5 /h) in a representative clinical cohort of different pre-test probabilities, could be integrated into medical decision-making and showed a good PPV of 0.8 for a PAT AHI ≥ 5/h or 0.86 for an AHI ≥ 15/h.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable data for negative PAT were found in the PATER study [ 31 ]. Previous studies have shown that PAT has a good sensitivity for an AHI ≥ 5/h (pooled sensitivity of 96%; CI 93–97%) [ 52 ]. The focus of our study was to determine how a positive PAT result (≥ 5 /h) in a representative clinical cohort of different pre-test probabilities, could be integrated into medical decision-making and showed a good PPV of 0.8 for a PAT AHI ≥ 5/h or 0.86 for an AHI ≥ 15/h.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 20 studies reported a diagnostic accuracy of 61% in classification of OSA severity category (normal, mild, moderate, and severe) comparing home sleep apnea testing vs polysomnography. A meta-analysis of PAT-based home sleep apnea testing that included 13 trials reported a sensitivity of 96% and a specificity of 44% for patients with an AHI of 5 or more events per hour, and it reported a sensitivity of 80% and a specificity of 90% for patients with an AHI of 30 or more events per hour. A comparison of concurrent polysomnography and PAT-based home sleep apnea testing device recordings of 500 patients suspected to have OSA found diagnostic concordance in 42% for mild, 41% for moderate, and 83% for severe OSA .…”
Section: Test Characteristicsmentioning
confidence: 99%
“…The polysomnography (PSG), conducted in a sleep laboratory by a trained physician, is widely recognized as the gold standard for OSA diagnosis [ 11 ]. Patients experiencing an average of at least 15 apnea events per hour are typically diagnosed with OSA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%